2009 International Conference on Power Engineering, Energy and Electrical Drives 2009
DOI: 10.1109/powereng.2009.4915163
|View full text |Cite
|
Sign up to set email alerts
|

Small-disturbance voltage stability of distribution systems with wind turbine implemented with WRIG

Abstract: The small-disturbance voltage stability of a gridconnected wound-rotor induction-generator (WRIG) windturbine system is analyzed under different operating conditions. This theoretical study shows the effect of the wound-rotor induction generator and its parameters on load-bus voltage collapse phenomena. Results show that the rotor resistance of the induction generators may decrease the system voltage stability margin and that the transmission line length has an important effect on the maximum loading point and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Small disturbance voltage stability is the ability of the power system, for a given initial operating condition, to maintain a steady voltage when subjected to a small disturbance such as an incremental change in load demand [18,73,74]. By making use of sensitivity information, factors affecting the small disturbance voltage stability can be determined.…”
Section: Small Disturbance Voltage Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Small disturbance voltage stability is the ability of the power system, for a given initial operating condition, to maintain a steady voltage when subjected to a small disturbance such as an incremental change in load demand [18,73,74]. By making use of sensitivity information, factors affecting the small disturbance voltage stability can be determined.…”
Section: Small Disturbance Voltage Stabilitymentioning
confidence: 99%
“…If Q-V sensitivity is positive for every bus, the system voltage is stable and vice versa [81,82]. Under various operating conditions, [73] carried out detailed analysis on grid-connected Wound Rotor Induction Generator (WRIG)-based wind turbine system to study the small disturbance voltage stability and concluded that the rotor resistance might reduce the voltage stability margin.…”
Section: Small Disturbance Voltage Stabilitymentioning
confidence: 99%
“…More sophisticated and well coordinated relaying schemes should be provided to realize the most appropriate protection methodology for wind farm elements [15]- [21]. Insufficient protective elements, non-integrated control scenarios and improper coordination among protective and control strategies may lead to serious problems for large grid-connected wind farms [22]- [27]. As example for these problems is the accident happening in North Germany on November 4, 2006.…”
Section: Power System Stability Overviewmentioning
confidence: 99%